BETWEEN OVERCOMING AND ADAPTATION: : THE JOURNEY OF PARALYMPIC ATHLETES IN THE HIGH-PERFORMANCE SPORTS SCENARIO (Interdisciplinary Studies Journal, 2026)
The Paralympic Games have established themselves over the years as the world's biggest sporting event dedicated to people with disabilities. This event not only celebrates sporting achievements, but also plays a crucial role in promoting inclusion and recognizing the abilities and potential of people with disabilities in sport. The aim of this study is to understand and analyze the process of sports initiation of people with disabilities into high-performance sport. Specifically, it seeks to analyze the factors that influence the entry and permanence of athletes in high-performance sport. The research has a qualitative, descriptive and cross-sectional approach. Ten Paralympic athletes who took part in the Tokyo 2020/2021 Paralympics were investigated. The instrument used was a semi-structured interview and a field diary to record the interviewees' facial expressions. Bardin's (2010) content analysis methodology was used to analyze the results, and the following categories were established: Disability, causes and impacts, Entry and permanence in sport and Regionalization of Brazilian Paralympic sport and the role of the Brazilian Paralympic Committee (CPB). It was concluded that late-acquired disability has a direct impact on the lives of people with disabilities and their family roles. It also emerged that paralympic athletes still face difficulties in entering and remaining in high-performance sport, including: lack of financial support, lack of qualified professionals, architectural obstacles and less media visibility.
Keywords: Athletes; Paralympic Games; People with disabilities